DSP implementation of an audio perceptual decoder - Ferreira, Vitor Manuel (2000)
In this work the audio spectral coder methodology was studied in order to achieve a real-time implementation of the decoder. This work followed two main steps: the study of an integrated solution for Pc developed in C++, and the development of the decoder in C. (...)